Discursiveness and History in the Central American Avant-Gardes - Bonilla Navarro, José Francisco (2022)
An approach is offered for the study of discursive manifestations of the avant-garde historical movements in Central American literature to delimit their aesthetic, ideological and thematic features in comparison with the aesthetic framework of the Spanish American avant-garde. Works by four writers are analyzed: Rafael Arévalo Martínez and Luis Cardoza y Aragón, in Guatemala; José Coronel Urtecho and Pablo Antonio Cuadra, in Nicaragua. The analysis of the texts attempts to fill a void that Central American literary criticism has not addressed for several decades, perhaps due to the lack of institutionalization that these artistic manifestations had in Central American countries.